Augmented Reality Learning Media on Geographic Symptoms to Increase University Students' Knowledge of Geographic Science: Pro-Environmental Behaviour - Ajat Sudrajat; Ojat Darojat; Sri Sumiyati; Ary Purwantiningsih; Syaeful Mikdar; Fitrah Jaya; Lisa Dwi Ningtyas (AL-ISHLAH: Jurnal Pendidikan, 2023)
In supporting difficult learning, innovative learning media are needed. One of the innovative learning media is augmented reality (AR). In this study, there is an AR design that is needed for the material of geographical phenomena. The method used is R D (Borg Gall, 2014). The results obtained in this study are AR designs for geographical phenomena (volcanoes, earthquakes, and tsunamis). It is hoped that the AR design for the material on geographical phenomena in this article can be useful in applying augmented reality material for geographical phenomena in social studies for lecturers who want to develop it as a learning medium for students.